Effects of sequence and storytelling methods on EFL development of an adult learner - Lee, S.J.; Pak, D. (KU Publ., 2021)
This article presents the effects of sequence and storytelling methods on an adult beginner learner’s English language development. Being a powerful and natural way to learn, convey, and retain information, these methods offer a number of benefits, such as improving learners’ language proficiency, increasing learner participation, providing learners with cultural experience and encouraging creativity. The following research questions guided the study: 1) How do sequence and storytelling methods motivate an adult language learner to improve English? 2) What linguistic aspects do sequence and storytelling methods develop in the learner’s English? A qualitative research approach, specifically a case study, was used to investigate these questions. The findings demonstrate that sequence and storytelling methods of teaching EFL positively contribute to English speaking proficiency and empowerment by motivating the learner. The participant of this case study appreciated the benefits of sequence and storytelling teaching techniques as they addressed her individual needs and increased her learning enjoyment, cultural awareness, and language ability.
Ересек оқушының ағылшын тілін шет тілі ретінде дамытуына тізбектік жəне баяндау əдістерінің əсері
Влияние методов последовательности и повествования на развитие английского как иностранного языка у взрослого учащегося
Keywords: EFL; sequence and storytelling methods; effects; an adult language learner; learner needs; motivation; empowerment; language proficiency